Evaluation of cumulative damage in glass fibre reinforced plastic by ultrasonic method - Srivastava, V.K.; Prakash, R. (Springer India, 1987)
This paper presents the cumulative damage in glass fibre reinforced plastic composite during loading and unloading at regular intervals using the continuous monitoring of ultrasonic test instrument. The result shows that the ultrasonic attenuation increases with an increase in the tensile load, which provides the change in internal damage of composites. © 1987 the Indian Academy of Sciences.
Keywords: Cumulative damage; E-glass fibre; epoxy resin; hounsfield tensemeter; tensile load; ultrasonic technique